Airplane (Usa Wonder House, 2022)
This delightful pop-up book is a wonderful means to introduce the young minds to the world of transport! Do you like ships? Do you want to learn more about them? Come with us and see what all they do in our huge world! Easy to read sentences Enhances reading skillsVivid illustrationsDevelops recognitionUnderstanding about transportsBuilds vocabulary
English stories
For children aged 7 - 10 years
Keywords: English stories